Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Guru Di Smk Budiniah Kabupaten Bogor - Andini, Yulia Putri; Agung, Syahrum; Suharti, Titing (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This research project is titled "The Effect of Work Environment and Organizational Culture on Teacher Performance at SMK Budiniah Bogor Regency," and it has the following research objectives: 1) to determine whether the work environment affects teacher performance at SMK Budiniah Bogor Regency; 2) to determine whether organizational culture affects teacher performance at SMK Budiniah Bogor Regency; and 3) to determine whether the work environment and organizational culture together affect teacher performance. An technique known as quantitative descriptive research is used for this study, with the sample size being set at 55 people drawn from Budiniah Vocational School in the Bogor Regency. At Budiniah Vocational High School in the Bogor Regency, both the work environment and the organizational culture have a significant impact on the performance of the teachers.